Implementation and preliminary evaluation of an entrepreneurship, biomedical innovation, and design pathway in a school of medicine curriculum - Nathaniel Hafer; Christian Keenan; Anindita Deb (Journal of Clinical and Translational Science)
New educational curricula are emerging to train physicians for healthcare in the 21st century. The University of Massachusetts Chan Medical School T.H. Chan School of Medicine (UMass Chan) implemented an MD curriculum redesign in the fall of 2022 that included seven educational pathways, including Entrepreneurship, Biomedical Innovation, and Design. This new pathway curriculum introduces students to the principles of innovation, entrepreneurship, basic engineering principles, and technology commercialization. It is modeled after the I-Corps curriculum with added material regarding engineering principles. I-Corps was initially developed by the National Science Foundation (NSF) to help scientists understand the commercial potential of their inventions. Major elements include the Business Model Canvas and Customer Discovery [19-22]. First-year (Class of 2027) and second-year (Class of 2026) pathway students were invited to participate in online surveys evaluating course material and their knowledge of course content. Initial results show that the program was well received and student self-assessment demonstrated significant improvement. Objective student knowledge also significantly improved. Novel curricula have the potential to transform medical education and prepare future physicians to practice healthcare in the 21st Century.